PERAN KOMUNIKASI ORGANISASI TERHADAP PARTISIPASI ANGGOTA KOPERASI MAHASISWA (STUDI KUALITATIF PADA ANGGOTA KOPERASI MAHASISWA BS UPI) - Iwang Puspa Negara; Ayub Ilfandy Imran (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Koperasi Mahasiswa BS UPI Koperasi is one of student cummunity in Uinversitas Pendidikan Indonesia which maintaning in cooperative specific field. Koperasi Mahasiswa BS UPI maintaining trade and service business. Koperasi Mahasiswa BS UPI is cooperative which have many achievement in west java consist of 4 coach, 2 supervisor, 24 center management and 3000 members. In spite that Koperasi Mahasiswa BS UPI have many members but level of member participation still lower, while participation is the important thing for Koperasi Mahasiswa. Higher or lower number of member participation is relate to how center management build their communication with member. The methods used in this research is qualitative approach by interview toward informant consist 1 couch, 2 center management and 3 members, observation and documentation. The purpose of this research to explained role of communication organization in Koperasi Mahasiswa BS UPI towards of members participation. Based on the result of the research,it can be known that role of communication organization which build from event and commitee is effective for increasing of members participation.